A Scientometric Analysis of Digital Financial Inclusion and Sustainability - Rehna John M; Vidhya Vinayachandran (Business, Management and Economics: Research Progress Vol. 8, 2024)
The importance of digital financial inclusion is critical in ensuring universal access to digital financial services, thereby fostering sustainable economic growth. The study of digital financial inclusion and sustainability has gained significant importance in recent times. Achieving sustainable development goals, lowering inequality, and strengthening economic integration depends on the successful integration of digital technologies into financial institutions and trade procedures. The study aims to analyse the popularity of digital financial inclusion and sustainability worldwide. It presents the country-wide publications, related research done, network clusters, citation trends and the like. This research presents a straightforward analysis using the Scopus database and VOSViewer, encompassing a thorough examination of the co-occurrence of author keywords and collaborative countries etc., in 319 selected documents. The upward trend in publication activity becomes apparent from 2016 onwards. The majority of publications fall within the domain of Social Sciences, followed by Economics, Econometrics, and Finance. Key topics garnering the most attention include financial inclusion, sustainable development, finance, sustainability, and economic growth. The study also outlines implications for facilitating the seamless adoption of digital financial inclusion and promoting sustainable growth.